(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
This study examined the provision and utilization of e-learning facilities for effective teaching-learning outcome in universities in Rivers State, Nigeria. The study adopted the descriptive research survey design. Three research questions and hypothesis were formulated to guide the study. The population of the study comprised of three thousand one hundred seventy six (3,176) academic staff in the three public universities in Rivers State, Nigeria. A sample size of two hundred and seventy (270) academic staff was selected in the three public universities in Rivers State, Nigeria representing 8.5% of the entire population using proportionate sampling technique. Structured four-point scale questionnaire titled: Provision and Utilization of E-Learning for Effective Teaching-Learning Outcome Questionnaire (PUELFETLOQ)” was validated and ensured for data collection. The instrument yielded the reliability index of 0.82. The research questions were answered using mean and standard deviation while the hypothesis was analysed using z-test statistics at 0.05 level of significance. The findings indicated that provision, utilization and possible means of managing e-learning facilities engenders effective teaching-learning outcome in universities in Rivers State, Nigeria. It was recommended among others that government should provide sufficient and quality e-learning facilities to all the universities in Rivers State, Nigeria to ensure effective teaching-learning outcome.